ANALISIS KONSUMSI BAHAN BAKAR SEPEDA MOTOR YANG DIGUNAKAN SEBAGAI TENAGA PUTAR POMPA - Mukhamad Khumaidi Usman; Syaefani Arif Romadhon (University of Muhammadiyah Jakarta, 2017)
Dry season is one of complicated problem for farmers in cultivating, because water is the main requirement for plant whereas there is no enough irrigation. One of the solution is using water pump, it takes ground water to irrigate rice field. But we need to make it more simple and more efficient using motorcycle activator 110 cc. This research used comparison between fuel consumption and water flow by pump. From research finding with water flow motorcycle activator of 46.8 m3/hour with fuel consumption of 0.751/hour whereas the use of irrigation water pump engine flow of 36 m3/hour with fuel consumption by 1,81/hour. From the discussion of the findings, it can be concluded that water pump using motorcycle activator, it is more economical of fuel consumption and it is bigger of water flow. Beside that it is more simple to bring it into rice field.